Extending the mutation spectrum for Galloway–Mowat syndrome to include homozygous missense mutations in the WDR73 gene. Issue 4 (5th January 2016) - Rosti, Rasim O.; Dikoglu, Esra; Zaki, Maha S.; Abdel‐Salam, Ghada; Makhseed, Nawal; Sese, Jordan C.; Musaev, Damir; Rosti, Basak; Harbert, Mary J.; Jones, Marilyn C.; Vaux, Keith K.; Gleeson, Joseph G.
Abstract : Galloway–Mowat syndrome is a rare autosomal‐recessive disorder classically described as the combination of microcephaly and nephrotic syndrome. Recently, homozygous truncating mutations in WDR73 ( WD repeat domain 73 ) were described in two of 31 unrelated families with Galloway–Mowat syndrome which was followed by a report of two sibs in an Egyptian consanguineous family. In this report, seven affecteds from four families showing biallelic missense mutations in WDR73 were identified by exome sequencing and confirmed to follow a recessive model of inheritance. Three‐dimensional modeling predicted conformational alterations as a result of the mutation, supporting pathogenicity. An additional 13 families with microcephaly and renal phenotype were negative for WDR73 mutations. Missense mutations in the WDR73 gene are reported for the first time in Galloway–Mowat syndrome. A detailed phenotypic comparison of all reported WDR73 ‐linked Galloway–Mowat syndrome patients with WDR73 negative patients showed that WDR73 mutations are limited to those with classical Galloway–Mowat syndrome features, in addition to cerebellar atrophy, thin corpus callosum, brain stem hypoplasia, occasional coarse face, late‐onset and mostly slow progressive nephrotic syndrome, and frequent epilepsy. © 2016 Wiley Periodicals, Inc.